Effects of amnesia on processing in the hippocampus and default mode network during a naturalistic memory task: A case study. (September 2019) - Oedekoven, Christiane S.H.; Keidel, James L.; Anderson, Stuart; Nisbet, Angus; Bird, Chris M.
Abstract: Despite their severely impaired episodic memory, individuals with amnesia are able to comprehend ongoing events. Online representations of a current event are thought to be supported by a network of regions centred on the posterior midline cortex (PMC). By contrast, episodic memory is widely believed to be supported by interactions between the hippocampus and these cortical regions. In this MRI study, we investigated the encoding and retrieval of real life-like events (video clips) in a patient with severe amnesia likely resulting from a stroke to the right (and possibly the left) thalamus, and a group of 20 age-matched controls. Structural MRI revealed grey matter reductions in left hippocampus and left thalamus in comparison to controls. We first characterised the regions activated in the controls while they watched and retrieved the videos. There were no differences in activation between the patient and controls in any of the regions. We then identified a widespread network of brain regions, including the hippocampus, that were functionally connected with the PMC in controls. However, in the patient there was a specific reduction in functional connectivity between the PMC and a region of left hippocampus when both watching and attempting to retrieve the videos. A follow up analysis of the control group revealed that, when watching the videos, the functional connectivity between these two regions was correlated with memory performance. Taken together, these findings support the view that the interactions between the PMC and the hippocampus enable the encoding and retrieval of naturalistic events. Highlights: We collected functional MRI data while an adult with amnesia and 20 controls watched and attempted to retrieve several videos. Functional connectivity between left hippocampus and posterior midline cortex was reduced in the patient compared to controls. In the controls, functional connectivity between the same two regions when watching the videos correlated with memory recall. This support the view that interactions between the hippocampus and neocortex underpin memory for naturalistic events.